2009
DOI: 10.1002/adfm.200901139
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Nucleic Acids through the Controlled Disassembly of Multifunctional Nanocomplexes

Abstract: An error occurred in the sequence of the antisense oligonucleotide shown in the supporting information file of this manuscript. New, corrected supporting information can now be found on its Wiley InterScience abstract page. Information was also missing from the caption of Figure 5; the corrected caption is as follows: Figure 5. a) Flow cytometry experiment showing the fluorescence intensity of PC-3 cells incubated with Cy3-labeled AON (400 nM) free, complexed to G5 PAMAM or entrapped in plain or Fab 0-PEG 115-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…a similar pattern to the cytotoxicity, Table S1). However, it should be claimed that although the effect of PEG on reducing cytotoxicity of cationic nanoparticles has been studied extensively and is in agreement with the current study, 30,31 there have not been detailed studies regarding the immunotoxicity of PEG. The development of PEG-specific antibodies after the injection of unloaded ( i.e.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…a similar pattern to the cytotoxicity, Table S1). However, it should be claimed that although the effect of PEG on reducing cytotoxicity of cationic nanoparticles has been studied extensively and is in agreement with the current study, 30,31 there have not been detailed studies regarding the immunotoxicity of PEG. The development of PEG-specific antibodies after the injection of unloaded ( i.e.…”
Section: Resultssupporting
confidence: 88%
“…PEGylation of poly(amidoamine) dendrimer-based complexes has been found in a previous study to impart greater stability to siRNA, as compared to siRNA/dendrimer complexes. 30 At 2 h, PEG-5%-cSCKs afforded higher stability for siRNA than did PEG-micelles. On the contrary, the opposite pattern was observed at 24, 48 and 72 h. The crosslinking might reduce the accessibility of nucleases in the first 2 h, however, the flexibility of non-crosslinked PEG-micelle chains to efficiently complex siRNA might explain this greater stability than the crosslinked nanoparticles.…”
Section: Resultsmentioning
confidence: 95%
“…At the same time, these nanoparticles are designed to lose their PEG-shell at cell surfaces or in the acidifying endosomes to facilitate their release into the cytoplasm. 13, 19, 20 Other hydrophilic polymers have also been used to coat the surface of nanoparticles, such as, poly(acrylic acid) (PAA), poly( N -vinylpyrrolidone), poly( N -isopropylacrylamide) and poly(carboxybetaine). The latter is another promising class of shell-forming polymers.…”
Section: Rational Design Of Polymeric Nanoparticlesmentioning
confidence: 99%
“…Worth mentioning is that unimolecular structures can be also utilized as building blocks for polymeric nanoparticles ( e.g. the use of dendrimers as core forming block of micelles 19, 43 and polymer brushes to construct cylindrical nanostructures 50 ) (Fig. 6).…”
Section: Polymeric Nanoparticles As Versatile Nanomedicine Platformsmentioning
confidence: 99%
“…Our group and others have shown that cellular uptake is not always correlated with transfection efficiency. 4,21 The lower transfection of nanoparticles might be related to the higher stability of the complexes that partially retard the release of siRNA intracellularly. For instance, Leroux and coworkers have found that amine functionalized poly(glycerol methacrylate) linear polymer induced higher bcl-2 oncoprotein knockdown as compared to the star-shaped analogue, although the latter demonstrated higher antisense oligonucleotide binding efficiency.…”
mentioning
confidence: 99%